The Effect of The Use of Geogebra on Understanding in Analytical Geometry Course - Nalim Nalim; Santika Lya Diah Pramesti; Fera Afriani (Program Studi Tadris Matematika IAIN Salatiga, 2022)
The main objective of this research is to analyze the effect of learning using Geogebra software on student learning outcomes in analytic geometry courses. The type of research used in this study is a quasi-experimental and data obtained by using test instrument testing, both pretest and posttest. The pretest that was first distributed was used to determine the students' initial abilities, while the posttest was given to determine the level of understanding (learning outcomes) of students. The population in this study were students in the fifth semester who took the Analytical Geometry Course at the Tadris Mathematics Study Program FTIK (Faculty of Tarbiyah and Teacher Training) IAIN Pekalongan. Respondents in this study consisted of two classes, namely the control class (class B) and the experimental class (class C). Analysis of the data used in this study is using the free sample t test. The results obtained concluded that there was no difference in learning outcomes between students who were given the Geogebra learning model and students who were given the conventional (conventional) learning model. This can be seen from the results of the t test, with a significance value of 0.126 0.05.